2020
DOI: 10.3390/molecules25153401
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mining of the Crotalus Spp. Venom Protease Repertoire Reveals Potential for Chronic Wound Therapeutics

Abstract: Chronic wounds are a major health problem that cause millions of dollars in expenses every year. Among all the treatments used, active wound treatments such as enzymatic treatments represent a cheaper and specific option with a fast growth category in the market. In particular, bacterial and plant proteases have been employed due to their homology to human proteases, which drive the normal wound healing process. However, the use of these proteases has demonstrated results with low reproducibility. Therefore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 105 publications
(124 reference statements)
2
11
0
Order By: Relevance
“…To identify and characterize proteins that confer resistance to metalloproteinase activity in the rattlesnake C. atrox , we used activity on a collagen-based substrate (Azocoll) as an initial assay for metalloproteinases and their inhibitors. Divalent cations such as Zn 2+ and Ca 2+ are critical for metalloproteinase function, and chelators such as EDTA inhibit their proteolytic activity ( 36 ). To test whether the activity of whole C. atrox venom on Azocoll was sensitive to EDTA, we added 1 millimolar (mM) EDTA and observed complete inhibition of the proteolytic activity, indicating that Azocoll was a suitable substrate for measuring the SVMP activity and its potential inhibition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To identify and characterize proteins that confer resistance to metalloproteinase activity in the rattlesnake C. atrox , we used activity on a collagen-based substrate (Azocoll) as an initial assay for metalloproteinases and their inhibitors. Divalent cations such as Zn 2+ and Ca 2+ are critical for metalloproteinase function, and chelators such as EDTA inhibit their proteolytic activity ( 36 ). To test whether the activity of whole C. atrox venom on Azocoll was sensitive to EDTA, we added 1 millimolar (mM) EDTA and observed complete inhibition of the proteolytic activity, indicating that Azocoll was a suitable substrate for measuring the SVMP activity and its potential inhibition ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyubiquitin-A isoform X2 may not only stimulate cell growth, protein kinases and relevant signalling, but also possess antibacterial activity [74][75][76] . Venom serine carboxypeptidase isoform X1 may help clotting via its thrombin-like activity 77 . In contrast, the upregulation of esterase B1 present in BnRJ-Zj is related to cell apoptosis and is detrimental to wound healing 78 .…”
Section: Discussionmentioning
confidence: 99%
“…from North and Central Americas are more abundant and have been widely investigated. These studies have shown hemostatic effects such as fibrino(geno)lytic and inhibition of platelet aggregation activities as well as local hemorrhage caused by degradation of the capillary basement membrane and muscle damage with lower regeneration (91)(92)(93). As C. d. ruruima venom composition differs from other more prevalent C. durissus subspecies envenomings, an antivenom based on oligoclonal mixtures of antibodies could be a strategy to improve treatment.…”
Section: Snake Venom Metalloproteases (Svmps)mentioning
confidence: 99%